Burden of tuberculosis among household children of adult multi drug resistant patients and their response to first line anti tubercular drugs - Rufaida Mazahir; Farzana K. Beig; Zuber Ahmed; Shahzad Alam (SpringerOpen, 2017)
Objective: The objective of the study was to find the prevalence and incidence of tuberculosis among household contacts of adult Multi Drug Resistant-tuberculosis (MDR-TB) patients and to evaluate their response to first line anti-tubercular drugs. Materials and methods: This prospective observational study was conducted from January 2014 to August 2015 at a tertiary care center in India. We included child contacts of ≤14 year age of recently diagnosed adult MDR-TB patients. Detailed demographic, socio-economic and treatment history including previous treatment, MDR suspect criterion, and HIV status of the index case was collected. Enrolled children were screened for tuberculosis at initial screening as well as during each follow up visit. Extra-pulmonary or sputum negative pulmonary cases were treated in category I. Sputum positive patients were treated as per sensitivity report. All children were followed up for a period of 1 year. Results: Eighty contacts of 21 index cases were enrolled. Disease prevalence at initial screening was 11.3% (n-9) and incidence on follow up was 1.4% (n-1). Prevalence of latent infection was 23.8% with incidence of 15.4% on follow up. Two patients were found to be sputum positive both sensitive to first line drugs. Failure rate of initial treatment was 10% (n-1). This child was initially sputum positive and sensitive to first line drug, but was later found to have MDR-TB. Conclusion: Mild disease in child contacts of MDR-TB can still show good respond to first line treatment especially in areas with high disease burden.